The international monetary system : essays in world economics - Cooper, Richard N. (London : MIT Press, 1987)
Prolegomena to the choice of an international monetary system -- The gold standard : historical facts and future prospects -- Flexing the international monetary system : the case for gliding parities -- Flexible exchange rates, 1973-1980 : how bad have they really been? -- The balance-of-payments adjustment process -- IMF surveillance overfloating exchange rates -- Eurodollars, reserve dollars, and asymmetries in the international monetary system -- The future of the dollar -- Sterling, European monetary unification, and the international monetary system -- The future of the SDR -- The international monetary system in the 1980s -- The evolution of the International Monetary Fund towards a world central bank -- Amonetary system forthe future.
Includes bibliographies and indexes.
Keywords: International finance